A coleção de Seis Peças para Principiantes, para violino e piano, de George Marinuzzi como material suplementar ao repertório do método Suzuki - Paula Cordeiro Franco (2016)
The violinist, composer, conductor and pedagogue George Marinuzzi was an important personality at Minas Gerais artistic scene in the 20th Century. In his career, stood out his role as the first violin professor at the Minas Gerais Music Conservatory, which later became the Federal University of Minas Gerais School of Music. As a composer, we highlight the Six Pieces for Beginners, focus of this research. Through the analysis of violin technique elements and pedagogical goals inherent to Marinuzzis pieces and to the pieces from the first and second volumes of the Suzuki Method, we made a comparative analysis between both repertoires. From this analysis, we elaborated a proposal for the use of the Six Pieces for Beginners as supplementary material to the Suzukis repertoire. Beyond the technical-pedagogical results of this work, we also present a gathering of George Marinuzzis biographic data, based on an extensive explorative research at his family archives. This way, we believe we are contributing to the rescue of the memory and work of this Minas Gerais musician.